2001
DOI: 10.1159/000064616
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Motor Cortex Stimulation for Phantom Limb Pain: Correlations between Pain Relief and Functional Imaging Studies

Abstract: Chronic motor cortex stimulation (CMCS) has provided satisfactory control of pain in patients with central or trigeminal neuropathic pain. We used this technique in 3 patients with intractable phantom limb pain after upper limb amputation. Functional magnetic resonance imaging (fMRI) correlated to anatomical MRI permitted frameless image guidance for electrode placement. Pain control was obtained for all the patients initially and the relief was stable in 2 of the 3 patients at 2 year follow-up. CMCS can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…Initial reports suggested that approximately 70% of patients had continued beneficial effect after 1 year. Subsequently, several authors have reported on the effectiveness of MCS for the treatment of both central and peripheral deafferentation pain, including trigeminal neuropathic pain, phantom limb pain and poststroke pain [6][7][8][12][13][14]. Overall, it appears that between 50 and 75% of patients achieve some long-term benefit from MCS.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports suggested that approximately 70% of patients had continued beneficial effect after 1 year. Subsequently, several authors have reported on the effectiveness of MCS for the treatment of both central and peripheral deafferentation pain, including trigeminal neuropathic pain, phantom limb pain and poststroke pain [6][7][8][12][13][14]. Overall, it appears that between 50 and 75% of patients achieve some long-term benefit from MCS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results allow many authors to consider fMRI as highly valuable before surgery for risk assessment, therapeutic decision making, and surgical planning in eloquent cortical areas (1,2,6,16,24,26,45,47,56,60,66). To our knowledge, only one team has tested this combination in a short preliminary series of NP patients (49,51,59). Indeed, Roux et al (49,51) and Sol et al (59) observed a correspondence between the two techniques.…”
Section: Interest Of Combining Fmri Guidance With Icm In Mcsmentioning
confidence: 94%
“…To our knowledge, only one team has tested this combination in a short preliminary series of NP patients (49,51,59). Indeed, Roux et al (49,51) and Sol et al (59) observed a correspondence between the two techniques. They suggested that fMRI guidance could help in guiding electrode positioning in MCS and could even replace iCM in detection of the CS.…”
Section: Interest Of Combining Fmri Guidance With Icm In Mcsmentioning
confidence: 99%
“…Although in many studies no adverse events with MCS have been reported, 16,18,19,[38][39][40]42,44 there have been some serious complications reported in the literature. Two epidural hematomas have been reported, one small and asymptomatic, 26 and the other requiring evacuation and associated with persistent dysphasia.…”
Section: Safety Of Mcsmentioning
confidence: 99%